Study on instability discriminating condition and permeability variation of triangle articulated structure in highly inclined goaf - Song Qin; Haifei Lin; Zongyong Wei; Wei Shen (Energy Exploration & Exploitation, 2022)
The huge, inclined goaf formed by the mining of steeply inclined and extra thick coal seams has the characteristics of occupying a large space and being subject to complex breaking behavior of its overlying rock structure, especially the rock block structure characteristics of the interface area between the goaf and the lower working face which is difficult to be characterized, leading to a hidden danger when mining the lower working face. In response to the aforementioned problems, the following conclusions are drawing as follows: (1) with the aid of the contradiction method, the critical condition governing instability of the triangular articulated structure was obtained to explain the correctness of the assumption of the triangular hinged structure; (2) three-point truss structure was composed of key layer blocks; (3) in the stabilization stage of the triangular hinged structure, the fracture network area was extracted, and the centerline intensive equivalent method of a single fracture segment was adopted to directly measure the equivalent length. Meanwhile, the value of equivalent average width with the equivalent length of a single crack was calculated by integral operation and equivalent figure calculation; (4) the mathematical expressions of permeability which was positively exponential function related to the ratio of equivalent average width to equivalent length were derived. Furthermore, the vectorized solution of seepage rate was carried out respectively for the goaf area and the extracted network area by using COMSOL software. The distribution of the strong seepage area of CBM and the ratio of equivalent average width to equivalent length is found to be consistent to a large extent, which provides theoretical support for subsequent CBM management.